The Effect of Due Professional Care, Competence, Work Experience and Auditor Independence on Audit Quality - Zaenis, Tiara; Hanum, Ayu Noviani; Alwiyah, Alwiyah (Economics and Business International Conference Proceeding, 2024)
This study aims to describe and analyze the Influence of Due Professional Care, Competence, Work Experience and Independence of Auditors on Audit Quality (Case Study on Public Accounting Firms in Semarang City). The population in this study is all Auditors working at Public Accounting Firms in Semarang City, producing 77 respondents as a sample. The data was collected by distributing the questionnaire directly using the Convenience Sampling method and then analyzed with SPSS 25.0 for windows. The test results were obtained that Due Professional Care had a positive effect on audit quality, Competence had no effect on audit quality, Work experience had no effect on audit quality and Independence had a positive effect on audit quality.